2001
DOI: 10.1007/s001340100993
|View full text |Cite
|
Sign up to set email alerts
|

Total extracorporeal arteriovenous carbon dioxide removal in acute respiratory failure: a phase I clinical study

Abstract: Pumpless extracorporeal AVCO2R is capable of providing complete extracorporeal removal of carbon dioxide during acute respiratory failure, while maintaining mild to moderate hypercapnia. Applied in conjunction with mechanical ventilation and permissive hypercapnia, AVCO2R resulted in normalization of arterial PCO2 and pH and permitted significant reductions in the level of mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…The amount of removed carbon dioxide depends closely on Pa,CO 2 and sweep gas flow according to the current data. CONRAD et al [26] observed in their analysis of contributing factors to carbon dioxide transfer a significant regression to Pa,CO 2 , pH, sweep gas flow and blood flow through the device.…”
Section: Effects On Oxygen Transportmentioning
confidence: 98%
See 1 more Smart Citation
“…The amount of removed carbon dioxide depends closely on Pa,CO 2 and sweep gas flow according to the current data. CONRAD et al [26] observed in their analysis of contributing factors to carbon dioxide transfer a significant regression to Pa,CO 2 , pH, sweep gas flow and blood flow through the device.…”
Section: Effects On Oxygen Transportmentioning
confidence: 98%
“…The quantity of carbon dioxide removed through the iLA in the current patients, was 148 mL?min -1 , which accounted for ,50% of total calculated carbon dioxide production. CONRAD et al [26] and ZWISCHENBERGER et al [24] reported in their small clinical trials on eight and five patients, respectively, complete and 70%, respectively, removal of carbon dioxide with the use of an Affinity oxygenator (Medtronic, Minneapolis, MN, USA). This oxygenator has a surface area of 2.5 m 2 , which is almost double the size of the Novalung oxygenator.…”
Section: Effects On Oxygen Transportmentioning
confidence: 99%
“…The ECCO2R method demonstrated significant removal of CO 2 in both mathematical and animal models, as well as in a small-scale phase I clinical trials (7,8). These models and studies showed the removal of CO 2 and blood-flow rates at approximately 112 mL/min and > 500 mL/min, respectively (9).…”
Section: Discussionmentioning
confidence: 86%
“…Mathematical simulations show that, with a sweep gas-to-blood flow ratio > 5, and by using an extracorporeal shunt fraction that is 10% to 15% of cardiac output, it is possible to achieve total CO 2 removal (7). Quantification of CO 2 removal is possible by using capnometry or mass spectrometry, which involves employing the product of the sweep-gas flow rate and the fraction of expired CO 2 (7). The patient illustrated the difficulties associated with a case exhibiting hypercapnia that required ECCO2R.…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical study of AV-ECCO 2 R commenced in 1997 5 and the first commercially available AV-ECCO 2 R system was released in 2002 (iLA Membranventilator ® , Novalung GmbH, Hechingen, Germany). AV-ECCO 2 R is by far the most widely used ECCO 2 R technique to date (Figure 2).…”
Section: Av-ecco 2 Rmentioning
confidence: 99%